2010
DOI: 10.1002/polb.22095
|View full text |Cite
|
Sign up to set email alerts
|

Chemically induced phase separation in the preparation of porous epoxy monolith

Abstract: A methodology for preparing porous epoxy monolith via chemically induced phase separation was proposed. The starting system was a mixture of an epoxy precursor, diglycidyl ether of bisphenol‐A (DGEBA), a curing agent, 4,4′‐diaminodiphenylmethane (DDM), and a thermoplastic polymer, polypropylene carbonate (PPC). As DGEBA was cured with DDM, the system became phase‐separated having PPC particles dispersed in epoxy matrix. After PPC particles were removed by thermal degradation, a porous structure was obtained. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 18 publications
(20 reference statements)
2
13
0
Order By: Relevance
“…1) for APOP at ambient temperature and at 70°C and also by larger sizes of particles formed at higher temperature. With respect to the low content of POPs, which is apparently below the critical volume fraction, the phase separation that gives rise to the structure of POP particles in epoxy matrix proceeds by nucleation and a growth mechanism 26, 27. Figure 1 shows further evidence of a significant increase in particle size with clay content found for nonreactive POP compared with APOP.…”
Section: Resultsmentioning
confidence: 87%
“…1) for APOP at ambient temperature and at 70°C and also by larger sizes of particles formed at higher temperature. With respect to the low content of POPs, which is apparently below the critical volume fraction, the phase separation that gives rise to the structure of POP particles in epoxy matrix proceeds by nucleation and a growth mechanism 26, 27. Figure 1 shows further evidence of a significant increase in particle size with clay content found for nonreactive POP compared with APOP.…”
Section: Resultsmentioning
confidence: 87%
“…In contrast, there was a significant dependence of the particle size on the curing temperature, with an increase in size from ∼ 100 nm at 20°C to ∼ 300 nm at 80°C. This increase undoubtedly corresponds to phase separation via nucleation and growth mechanism expected for the low concentrations of the second phase polymer28–30 that we used. A similar increase in the particle size with increasing temperature has been reported for analogous epoxy systems by others 28, 31, 32.…”
Section: Resultsmentioning
confidence: 89%
“…8 In these cases, 1-decanol was poor solvent, and cyclohexanol acted as a good solvent for the polymer. Therefore, it usually needs tedious experiments to search for the designed structure of 3D bicontinous skeleton; Jianhua Li et al 18,19 have made a serious of research to regulate the polymer structures, and found that the average pore size increased with increasing porogen concentration, increasing curing temperature, and decreasing the content of curing agent. 9 These morphological changes mainly resulted from the difference between reaction and phase separation rates in various porogenic solvents.…”
Section: Introductionmentioning
confidence: 99%